Interference With Coagulation Cascade as a Novel Approach to Counteract Cisplatin-Induced Acute Tubular Necrosis; an Experimental Study in Rats - Mohamed G. Ewees; Basim A. S. Messiha; Ali A. Abo-Saif; Ali A. Abo-Saif; Asmaa M. A. Bayoumi; Mohamed S. Abdel-Bakky; Mohamed S. Abdel-Bakky (Frontiers Media S.A., 2018)
Coagulation system activation plays an important role in the pathophysiology of different diseases. In spite of massive research regarding cisplatin-induced nephrotoxicity, the role of coagulation cascade in such toxicity is still questionable. Here, we aim to investigate the role of activation of coagulation system in the initiation of cisplatin-induced acute renal tubular necrosis. Moreover, the role of the anticoagulant rivaroxaban against such toxicity was investigated. Briefly, animals were classified into seven groups, eight rats each. Group 1 served as normal control group, groups (2-7) received i.p. single doses of cisplatin (6 mg/kg b.w), groups (6-7) were treated with rivaroxaban (5 and 7 mg/kg b.w, p.o., respectively) 7 days before cisplatin injection and completed for 4 days. Animals in groups (2, 3, and 4) were sacrificed after 1, 2 and 3 days of cisplatin injection, respectively, while groups (1, 5, 6, and 7) were sacrificed after 4 days of cisplatin injection. Serum cystatin-c, urea, creatinine and γ-glutamyl transferase, urinary Lipocaline-2, and KIM-1 protein densities, as well as glomerular filtration rate (GFR) were assessed. Immunofluorescence examination of glomeruli fibrin and tissue factor (TF) was also performed coupled with a histopathological study. Cisplatin administration increased expression of fibrin and TF starting 24 h of cisplatin injection even before renal failure markers elevated. Leukocytosis, thrombocytopenia, and increased prothrombin time were also observed. Cisplatin also induced tubular damage evidenced by increased serum cystatin-c, urea, and creatinine with significant decrease in GFR and Gamma glutamyl transferase (GGT) activity. Rivaroxaban significantly decreased elevation of fibrin and TF with significant reduction in serum creatinine, BUN and cystatin-c levels. Rivaroxaban also significantly improved hematological markers and histological features as well. This study showed that activation of coagulation system plays an important role in the pathophysiology of cisplatin-induced acute renal tubular damage. Interference with coagulation cascade may be a promising nephroprotective strategy against chemical nephrotoxicity.